Skeletal changes in patients with mandibular prognathism after mandibular set back and bimaxillary surgery – A comparative cephalometric study - Sinobad, Vladimir; Strajnić, Ljiljana; Sinobad, Tamara (Vojnosanitetski pregled, 2021)
Bacground/Aim. Recently, maxillary and bimaxillary surgery gained the primacy in the surgical correction of class III deformities. The aim of this investigation was to compare the changes in the skeletal relationships in patients with mandibular prognathism after bimaxillary surgery. Methods. The study included 70 subjects divided into three groups. Twenty class III patients of the experimental group 1 underwent bilateral sagittal ramus osteotomy and twenty patients of the experimental group 2 were subjected to bimaxillary surgery. The control group consisted of 30 subjects with skeletal class I and physiological occlusion. Cephalometric research was conducted on 110 lateral cephalometric radiographs made in subjects of the experimental groups 1 and 2 before and after surgery and in subjects of the control group. Using the computer program “Dr. Ceph”, 30 linear and angular skeletal variables were analyzed on each radiograph. Results. Bimaxillary osteotomies changed most of variables that characterize the mandibular prognathism. The changes in the sagittal plane included the significant increase of sella-nasion to the A point (SNA) angle (by 4º on the average) and the A point to B point (ANB) angle (6°), and significant reduction in angles sella-nasion to the B point (SNB) (3º), gonial angle (ArGoMe) (8°), gonial angle inferior (NGoMe) (6.2º), and Björks sum (7°). The vertical relationships were normalized by significant reduction in overall anterior face height N-Me (by 5 mm on the average), the lower anterior face height ANS-Me (4 mm), significant increase in the total posterior face height S-Go (2.5–3 mm), lower posterior face height PNS-Go (4 mm), and significant reduction of the basal and mandibular plane angles. Conclusion. Compared to the isolated mandibular operations, bimaxillary surgery changes more efficiently the sagittal and vertical skeletal relations in patients with class III deformities and harmonizes more successfully the entire skeletal facial profile.